Innovative strategy for in-office tooth bleaching using violet LED and biopolymers as H2O2 catalysts - Martins, Beatriz Voss [UNESP]; Dias, Marlon Ferreira [UNESP]; de Oliveira Ribeiro, Rafael Antônio [UNESP]; Leite, Maria Luísa de Alencar e Silva [UNESP]; Hebling, Josimeri [UNESP]; de Souza Costa, Carlos Alberto [UNESP] (Elsevier, 2022)
Objective: To assess the influence of coating the enamel with a nanofiber scaffold (NS) and a polymeric catalyst primer (PCP) on the esthetic efficacy, degradation kinetics of hydrogen peroxide (H2O2), and trans-amelodentinal cytotoxicity of bleaching gels subjected or not to violet-LED irradiation. Methodology: The following groups were established (n = 8): G1- No treatment (negative control); G2- NS+PCP; G3- LED; G4- NS+PCP+LED; G5- 35% H2O2 (positive control); G6- NS+PCP+35% H2O2+LED; G7- 20% H2O2; G8- NS+PCP+20% H2O2+LED; G9- 10% H2O2; G10- NS+PCP+10% H2O2+LED. For esthetic efficacy analysis, enamel/dentin discs were stained and exposed for 45 min to the bleaching protocols. To assess the cytotoxicity, the stained enamel/dentin discs were adapted to artificial pulp chambers, and the extracts (culture medium + components diffused through the discs) were collected and applied to MDPC-23 cells, which had their viability, oxidative stress, and morphology (SEM) evaluated. The amount of H2O2 diffused and hydroxyl radical (OH•) production were also determined (two-way ANOVA/Tukey/paired Student t-test; p < 0.05). Results: G6 had the highest esthetic efficacy compared to the other groups (p < 0.05). Besides the esthetic efficacy similar to conventional in-office bleaching (G5; p > 0.05), G10 also showed the lowest toxic effect and oxidative stress to MDPC-23 cells compared to all bleached groups (p < 0.05). Conclusion: Coating the enamel with a nanofiber scaffold and a polymeric catalyst primer, followed by the application of 10%, 20%, or 35% H2O2 bleaching gels irradiated with a violet LED, stimulates H2O2 degradation, increasing esthetic efficacy and reducing the trans-amelodentinal toxicity of the treatment.
Keywords: Cytotoxicity; Odontoblasts; Tooth bleaching; violet